DEIKSIS PADA CHANNEL YOUTUBE OFFICIAL HADIAH SPESIAL NADIEM MAKARIEM UNTUK NONO SI JENIUS MATEMATIKA: ANALISIS PRAGMATIK - Santa Rosa Br Pardosi; Sinta M Pasaribu; Frinawaty Lestarina Baru; Emasta Evayanti Simanjuntak; Sintya Klolanta Br Ginting (FKIP, Universitas Palangka Raya, 2023)
This study aims to analyze the various kinds of deixis contained in conversations on the Official Inews Youtube channel with the title